Efficiency of Soybean Farming Production Factors (Glycine max (L.) Merrill) in Bancak Hamlet, Gebyog Village, Mojogedang District, Karanganyar Regency - Mahananto; Wahyu Widayat; Alina Dian Aryani (Journal of Rural and Urban Community Studies, 2026)
This thesis was stack based on the result of research aimed at assessing the cost, revenues, and income of Soybean farming; to study the effect on the use of production factors on the production of soybean farming; and to assess economic efficiency level of inputs combination used on soybean farming in Bancak village, sub district Mojogedang, Karanganyar Regency. Basic method of the research descriptive analysis method and its execution is by survey technique. The research took one village who have the biggest soybean productivity in sub district Mojogedang. There are 30 respondents and taken by simple random sampling method. The result of this research showed that with the farming costs of soybean is Rp11,200,155.94/Ha/MT, the farming revenue of soybean farming is Rp14,242,574.26/Ha/MT, and that produce income amount of Rp3,042,418.32/Ha/MT. To study the effect of the use of production factors about production is used regression model with the Cobb Douglas produce function model modification. The correlation of the use of production factors with production of soybean is realized in the Cobb Douglas produce function model as this: Y = -0.176.X10,552.X20,836.X3-0.775. X4-0.495. X5-0.043. X6-0.021. X7-0.285. X80,908. X91,179 That equation was analyzed by double linear regression showed that the used of those production factors are affected to soybean production. Individually production factors the land area and the seeds also having real effect the soybean production, labour, Urea ferlitizers, Phonska ferlitizers, Gandasil B fertilizers, Gandasil D fertilizers, insecticides Apidor, level of graduated education, and experience of soybean farming are not real effect to soybean production. Pursuant to maximum advantage approach can be known that using inputs of soybean farming in has not efficient.